2015
DOI: 10.1371/journal.pone.0130651
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation-Guided Prediction of Clinical Failure in High-Risk Prostate Cancer

Abstract: BackgroundProstate cancer (PCa) is a very heterogeneous disease with respect to clinical outcome. This study explored differential DNA methylation in a priori selected genes to diagnose PCa and predict clinical failure (CF) in high-risk patients.MethodsA quantitative multiplex, methylation-specific PCR assay was developed to assess promoter methylation of the APC, CCND2, GSTP1, PTGS2 and RARB genes in formalin-fixed, paraffin-embedded tissue samples from 42 patients with benign prostatic hyperplasia and radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 59 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…This potential role for APC , GSTM2 and RARβ is already known [7,11,22,23,] but ALOX12 , MT1A and MYCL2 methylation are novel potential biomarkers that merit further validation. Identification of new methylation markers could depend on the population studied itself.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This potential role for APC , GSTM2 and RARβ is already known [7,11,22,23,] but ALOX12 , MT1A and MYCL2 methylation are novel potential biomarkers that merit further validation. Identification of new methylation markers could depend on the population studied itself.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, other variable DNA methylation alterations in neoplastic tissue samples have been also associated with the prediction of PSA recurrence after RP [10,17,18,19,20,21,22,23,24]. These studies have identified new potential tumor markers including methylation of PITX2 , HOXD3 , APC , TGFβ2 , RASSF1A , ANEP , PCDH10 , ZNF132 , TDRD1 , AOX1 , C1orf114 , GAS6 , HAPLN3 , KLF8 , MOB3B , CCND2 , PTGS2 , RARB , SRD5A2 and CYP11A1 , thus emerging as new predictors of BCR particularly in high-risk clinically localized disease.…”
Section: Discussionmentioning
confidence: 99%
“…Others have sought to relate CpG methylation patterns to clinical outcome and combined their patterns in univariate regression analyses of time to disease recurrence and revealed that methylation of certain loci, for example again including AOX1 and RARB [133] predicted disease progression [134,135]. Further supporting the relevance of DMR in PCa progression, the TCGA investigators revealed how altered DNA methylation patterns associated with different PCa genetic phenotypes.…”
Section: Prostate Cancer As a Model Of The Interplay Between Genommentioning
confidence: 99%
“…In 65% of the cases, the treatment recommendation changed after the genetic test, and in 40% there was reduction in treatment burden (interventional treatment changed to noninterventional). Although this study shows genomic tests can have a significant impact on treatment decisions, follow-up data were not reported to determine the long-term impact of these changes in management [83]. In another study involving 149 prostate cancer patients, the promoter methylation of seven genes was evaluated by methylation-sensitive PCR in tissue and urine samples.…”
Section: • Methylation Assaysmentioning
confidence: 97%